Listening evaluation and classification of female singing voice categories - Frič, Marek; Pavlechová, Angelika (Logopedics, Phoniatrics, Vocology, 2020)
Objective: Classification of voices into types depends on several factors: physiological - the size of the laryngeal and vocal tracts; acoustic-musically acceptable vocal range; position of formants; and properties of timbre. The aim of the study is to verify whether a group of experienced voice pedagogues and singers can determine the vocal type of the artist based on listening to a part of the aria better than a group of musicians can, and to determine what acoustic properties of the recordings are linked with the perceptual results of their evaluation.Methods: Freely available recordings of 11 females of different vocal categories of Rossini's aria "Una voce poco fa" from the opera Il Barbiere di Seviglia were selected for listening tests performed on examples of recitatives and coloraturas. Seven voice teachers (experienced group) and seven musicians non-teachers (laypeople group) evaluated the properties of the vocal category, timbre (dark-bright), resonance, vowel placement, suitability of vibrato, aesthetic impression, and voice flexibility.Results: The results showed a significantly higher inter-judge reliability in the experienced group. The highest reliability was achieved in timbre and vocal category evaluation, the least consistent was the evaluation of resonance. Factor analysis of the assessment variability showed dependent ratings of the vocal category, brightness and vowel placement for both groups in recitative. The experienced group similarly evaluated the brightness and the vocal category in coloratura. Assessment of the vocal category correlated with the reported categories of singers only in the experienced group. The categories mezzo-soprano and soprano were differentiated by spectral levels (based on FFT analysis of whole stimuli) in the 3.5-4.1 kHz spectral band in the recitative and in the 1.3-2.1 kHz and around 2.5 kHz bands in coloratura, and by the position of the local minimum after the fifth maximum for both kinds of stimuli.Conclusions: By means of correlation with ratings by experienced listeners, it is demonstrated that the voice category is mainly connected with the levels of specific spectral peaks, while brightness is correlated with the frequency positions of spectral maxima.
Keywords: Sex Factors; akustika; Humans; Acoustics; Sound Spectrography; Female; kvalita hlasu; Auditory Perception; lidé; mínění; Singing; sexuální faktory; zpívání; ženské pohlaví; Judgment; Voice Quality; zvuková spektrografie; odchylka pozorovatele; Observer Variation; sluchová percepce